Identifying Knowledge Acquisition Of Primary Class Students - Tashpulatova D.M. (Euro Asian Journal Publishing, 2024)
The article discusses the problem of diagnosis of primary school students' mastery of knowledge, and authors' methodical recommendations are presented.
Keywords: Education; elementary; student; knowledge